Words Like Birds : Sakha Language Discourses and Practices in the City - Ferguson, Jenanne, 1983- (Book collections on Project MUSE., 2019)
"An analysis of Sakha linguistic sensibilities and practices in the urban space of Yakutsk, capital of the Sakha Republic, based on research conducted in the early twenty-first century"--